Long-Term Results of Autologous Tooth Bone Grafting in Alveolar Cleft Reconstruction: A Retrospective Cohort Study - Tamás Würsching; Bence Mészáros; Eleonóra Sólyom; Bálint Molnár; Sándor Bogdán; Zsolt Németh; Krisztián Nagy (Biomedicines)
Background/Objectives: During alveolar cleft grafting, the use of autogenous cancellous bone harvested from the iliac crest is still considered the gold standard. Due to the risk of donor-site morbidity and excessive graft resorption, alternative grafting materials (e.g., intraoral bone, xenografts) are being tested. The aim of this study was to compare the efficacy of using an autologous tooth-derived graft material and iliac crest cancellous bone in the reconstruction of the alveolar cleft in patients with a unilateral cleft lip and palate. Methods: A total of 21 patients with a unilateral cleft lip and palate, who underwent alveolar bone grafting between 2020 and 2023 were included in the study. In 11 cases, the donor site was the iliac crest; in the rest of the cases, deciduous teeth were harvested, processed, and used as an autologous particulate graft material for alveolar reconstruction. The mean follow-up time was 30.0 months, CBCT scans were taken, and the results were compared based on the ranking system published by Stasiak et al. Results: The Wilcoxon signed-rank test showed that the amount of bone on the cleft side was significantly less than that on the contralateral non-cleft side (ATB: p = 0.002, iliac crest: p = 0.005). The Mann–Whitney U test showed that there were no significant differences in bone quantity on the cleft side between the two groups (U = 47.5, p = 0.617). Conclusions: The use of ATB might be a feasible alternative to autologous bone during alveolar cleft reconstruction. This type of graft shows long-term stability, which is comparable to the bone harvested from the iliac crest.